Detection of potentially anomalous cosmic particle tracks acquired with CMOS sensors: Validation of rough k-means clustering with PCA feature extraction - Hachaj, Tomasz; Piekarczyk, Marcin; Wąs, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
We present a method capable of detecting potentially anomalous cosmic particle tracks acquired with complementary metal-oxide-semiconductor (CMOS) sensors. We apply a principal components analysis-based feature extraction method and rough k-means clustering for outlier detection. We evaluated our approach on more than ten to the fourth power images acquired by the Cosmic Ray Extremely Distributed Observatory (CREDO). The method presented in this work proved to be an effective solution.
Keywords: cosmic-ray particle; rough sets; rough k-means; anomalies detection; principal components analysis; complementary metal-oxide-semiconductor sensors